Validation and adaptation of Motion Sickness Susceptibility Questionnaire – Short Form to the Portuguese language and population - Santos, Cristina (2025)
Cinetosis or motion sickness is a normal physiological response associated with the organism's exposure to motion or movement in the visual environment. The susceptibility and severity of this symptom can be assessed using the Motion Sickness Susceptibility Questionnaire – Short Form, a widely used instrument for measuring susceptibility to motion sickness, translated and validated in several languages. The present work aims to validate and adapt this questionnaire for the Portuguese language and population of Portugal. The methodology used in this paper was based on the principles of good practice for the process of translation and cultural adaptation of self-assessment instruments, resulting in the version of the Motion Sickness Susceptibility Questionnaire – Short Form in Portuguese from Portugal.